Knowledge paradigm in the prophetic tradition : an analytical study of the views of Bediuzzaman Said Nursi - Noor Azma binti Mohamad Khassim (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2007)
Bedi'uzzaman Sa'id Nursi (1876-1960) is a distinctive figure in modern Islamic history. His treatises known as Rasa’il al-Nur represent his mature thought. Various studies have been done in order to examine and analyse his thought. The present study attempts to look into his conception of Sunnah Nabawiyyah (Prophetic Tradition) and its relation to his epistemological view, focusing on the Sunnah as the source of knowledge. The study employs the inductive method and content analysis when dealing with Rasa’il al-Nur and other related sources from which his conception of Sunnah and epistemological views would be deduced. Historical and descriptive methods are applied to examine the historical events of Bedi 'uzzaman Sa'id Nursi and his biography. The study finds that Bedi 'uzzaman Sa'id Nursi’s conception of Sunnah is very wide, encompassing both Shari'ah and Haqiqah that are the physical and metaphysical aspects of Sunnah. Nevertheless, the physical aspect of Sunnah in the form of Shari'ah could not be separated from the metaphysical aspect which is attached to the Reality of Muhammad (al-Haqiqah al-Muhammadiyyah). Sunnah is of two kinds: al-Sunnah al-Kubra and al-Sunnah al-Sughra. Al-Sunnah al-Kubra is the Divine Laws, which is embodied in and appeared throughout the macrocosm and microcosm. While al-Sunnah al-Sughra is al-Sunnah al-Muhammadiyyah that consists of four types of Hadith: Hadith Qudsi, Hadith Qawli, Hadith Fi'li and Hadith Taqriri. Al-Sunnah al-Sughra is the translation of the Sunnah KubrÉ. In relation to the epistemology, Sunnah plays an important role as a source of true knowledge. The perfection in knowledge and the highest knowledge of God (ma'rifat Allah) could only be attained by the means of Sunnah. The Sunnah and other sources of knowledge, such as the human senses, the intellect, the conscience (wijdan), the Qur’an and the universe, are mutually self-affirming. In other word, the Sunnah and other sources of knowledge affirm each other. The study came to the conclusion that the Sunnah is the nexus between the servant ('abd) and his God, while the deviation from Sunnah will bring harm in both the temporal world (al-dunya) and the hereafter (al-akhirah).